2016
DOI: 10.1021/acs.estlett.6b00387
|View full text |Cite
|
Sign up to set email alerts
|

Field Validation of Supercritical CO2 Reactivity with Basalts

Abstract: Continued global use of fossil fuels places a premium on developing technology solutions to minimize increases in atmospheric CO 2 levels. CO 2 storage in reactive basalts might be one of these solutions by permanently converting injected gaseous CO 2 into solid carbonates. Herein, we report results from a field demonstration in which ∼1000 metric tons of CO 2 was injected into a natural basalt formation in eastern Washington state. Following post-injection monitoring for 2 years, cores were obtained from with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
125
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 17 publications
8
125
0
Order By: Relevance
“…The formation of ankerites and aluminosilicate minerals in this study agrees well with the experimental investigation by Gysi and Stefánsson [], which showed that precipitation of chemically zoned ankerite, ankerite‐dolomite solid solution, and amorphous silica predominate at temperatures <100°C. Moreover, McGrail et al [] in their recent extraction of a core from the Wallula CO 2 sequestration field show that ankerite nodules had formed in vugs and veins in the basalt around the injection well. Chemical profiles of selected nodules indicated that the ankerite were rich in Ca and Fe with minor amounts of Mn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of ankerites and aluminosilicate minerals in this study agrees well with the experimental investigation by Gysi and Stefánsson [], which showed that precipitation of chemically zoned ankerite, ankerite‐dolomite solid solution, and amorphous silica predominate at temperatures <100°C. Moreover, McGrail et al [] in their recent extraction of a core from the Wallula CO 2 sequestration field show that ankerite nodules had formed in vugs and veins in the basalt around the injection well. Chemical profiles of selected nodules indicated that the ankerite were rich in Ca and Fe with minor amounts of Mn.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonate precipitation occurred much faster than expected, and in 2 years, 95% of the injected carbon dioxide precipitated as carbonate minerals [ Matter et al , ]. The Wallula Basalt Pilot Project located in eastern Washington injected 1000 t of pressurized liquid CO 2 into the Columbia River Basalt formation in 2013 to a depth of 828–887 m [ McGrail et al , ]. A core extracted 2 years post‐injection showed evidence of secondary carbonate mineral precipitation in the form of ankerite throughout the rock vesicles [ McGrail et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The CarbFix CCS pilot in Iceland injected 230 tons of CO 2 dissolved in water into a basalt reservoir, and postinjection analysis showed 95% of the CO 2 was permanently converted to mineral phases just 2 years after injection . The Wallula Basalt Sequestration Pilot Project in eastern Washington injected 1000 metric tons (MT) of supercritical CO 2 into the Columbia River Basalt Group (CRBG) and postinjection analysis showed that carbonate nodules in sidewall cores were (i) widespread and (ii) composed of the same isotope signature as the injected CO 2 . To complement these results, CCS in deep basalt reservoirs is motivated to a large extent by the relatively high storage potential within both onshore and offshore basalt formations.…”
Section: Introductionmentioning
confidence: 99%
“…), and comprises a layered assemblage of ∼300 Miocene‐age flood basalts with an areal extent of 200 000 km 2 , aggregate thickness of 1–5 km, and total estimated volume of 224 000 km 3 . The CRBG has been extensively studied due to its wide range of resource potential, including (1) groundwater production, (2) nuclear waste storage, (3) natural gas storage, (4) geologic CO 2 sequestration, and (5) geothermal resources . Among the principal challenges in assessing the feasibility of engineered CRBG reservoirs is to understand how fracture‐controlled reservoir properties (i.e., permeability and porosity) affect both local‐ and regional‐scale fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation for this research grew out of a need for RMs in the wake of recent technical advances in carbonate δ 13 C and δ 18 O microanalysis by SIMS, and the potential applicability of this technique to intensifying research efforts concerned with geological carbon sequestration (McGrail et al . , Śliwiński et al . ).…”
mentioning
confidence: 99%